EDUKASI ANEMIA DAN STUNTING PADA BALITA SEBAGAI UPAYA PENINGKATAN STATUS GIZI DI DESA APUI KABUPATEN ALOR - Roslin E. M. Sormin; Heri Sutrisno; Akto Yudowaluyo; Yosefa S. Atok (Jurnal Abdi Insani, 2026)
Stunting and anemia remain major nutritional problems in children in remote areas of Indonesia, including mountainous regions such as Apui Village, Alor Regency. This activity aimed to provide health education and screen nutritional status and anemia in toddlers as a community-based prevention and control effort. The activity was conducted on July 24, 2025, in Apui Village using interactive lectures, discussions, anthropometric measurements (height, weight, mid-upper arm circumference), and hemoglobin (Hb) testing using a portable device on 38 toddlers and their mothers/caregivers. The prevalence of stunting (HAZ) was 34.2% and anemia (Hb <11 g/dL) was 47.4%, with a mean Hb level of 10.88 ± 1.70 g/dL. Although no significant statistical relationship was found between anemia and stunting (p=0.214), anemic children had 2.4 times greater risk of stunting. Active participation of mothers in discussion sessions showed high enthusiasm for the material presented. Anemia and stunting problems in Apui Village remain high. Integrated education with screening was successfully implemented and detected early cases of malnutrition, potentially serving as an intervention model in resource-limited areas.